1987
DOI: 10.1080/07315724.1987.10720191
|View full text |Cite
|
Sign up to set email alerts
|

The glycemic index: similarity of values derived in insulin-dependent and non-insulin-dependent diabetic patients.

Abstract: To see whether relative differences in the glycemic responses to different foods were similar in insulin-dependent (IDDM) and non-insulin-dependent diabetic patients (NIDDM) we determined the glycemic index (GI) of a total of 20 foods and mixed test meals in groups of IDDM and NIDDM volunteers. The mean GI values ranged from 32 in NIDDM and 41 in IDDM (pearled barley) to 105 in NIDDM and 111 in IDDM (bread with cheese and tomato). The correlation between the mean GI values in IDDM and NIDDM was highly signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 33 publications
(50 reference statements)
2
30
0
Order By: Relevance
“…This value is consistent with the calculated CVs from other reports with healthy volunteers, which ranged from 12 to 53% (3,(15)(16)(17). From a report evaluating the glycemic response to white bread (18), the mean among-subject CV for the AUC was calculated as 33% for subjects with type 2 diabetes and 39% for subjects with type 1 diabetes. Similarly, from a comparison of glycemic index values from different pasta foods in a sample of subjects with type 1 (57 Ϯ 20, n ϭ 6, CV ϭ 34%) and type 2 (49 Ϯ 23, n ϭ 11, CV ϭ 47%) diabetes, CVs were 34 and 47%, respectively (19).…”
Section: Conclusion -D E S P I T E T H Esupporting
confidence: 78%
“…This value is consistent with the calculated CVs from other reports with healthy volunteers, which ranged from 12 to 53% (3,(15)(16)(17). From a report evaluating the glycemic response to white bread (18), the mean among-subject CV for the AUC was calculated as 33% for subjects with type 2 diabetes and 39% for subjects with type 1 diabetes. Similarly, from a comparison of glycemic index values from different pasta foods in a sample of subjects with type 1 (57 Ϯ 20, n ϭ 6, CV ϭ 34%) and type 2 (49 Ϯ 23, n ϭ 11, CV ϭ 47%) diabetes, CVs were 34 and 47%, respectively (19).…”
Section: Conclusion -D E S P I T E T H Esupporting
confidence: 78%
“…Previous studies have shown that GI values are similar in healthy control vs T2DM (Jenkins et al, 1983), individuals with type 1 diabetes (T1DM) vs individuals with T2DM (Wolever et al, 1987), adults vs children with T1DM (Wolever et al, 1988), T2DM on oral agents vs insulin and T2DM in good vs poor metabolic control . We showed here that the GI values of foods in hyperinsulinemic subjects were similar to those in healthy control and T2DM subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Many foods have been tested for their GI values in healthy control or diabetic subjects (Foster-Powell et al, 2002). As the GI values of foods are similar in healthy control and diabetic subjects (Jenkins et al, 1983, Wolever et al, 1987, 1988, GI values tested in healthy control subjects can be applied in the nutritional management of diabetes (Atkinson, 2008). However, as GI has never been tested in non-diabetic subjects with insulin resistance/hyperinsulinemia, it is unknown whether GI is valid in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The glucose and insulin responses of different rye breads and other rye products have been reported to be variably lower than those of wheat bread, as reviewed by Foster-Powell & Brand Miller (1995). The lowest GI-values (66 ± 80) have been reported for pumpernickel-type breads containing intact kernels (Jenkins et al, 1985(Jenkins et al, , 1986Wolever et al, 1987Wolever et al, , 1994. There is a consensus that intact botanical structure protects the encapsulated starch of the kernel against the hydrolysis (Brand et al, 1990;Granfeldt et al, 1992).…”
Section: Introductionmentioning
confidence: 99%